Network Security Analysis Based on Internet Protocol Security Using Virtual Private Network (VPN) - rosyidah, aliyyah; Parenreng, Jumadi Mabe (Internet of Things and Artificial Intelligence Journal, 2023)
The network security system is continuously advancing alongside technological developments. VPNs, which utilize open networks, aim to provide security by leveraging IPSec to transmit private data through L2TP tunneling strategy from the server to the branch computer/client and vice versa. Conversely, it can also lead to poor security practices. VPNs are implemented using the layer 2 IPSec tunneling protocol with two MikroTik devices. Testing is conducted to assess the security and speed of the network using the command line and MikroTik Winbox, where the server monitors packet delays to determine the improvement in network security quality. This research has identified several weaknesses in implementing this VPN protocol, namely the need for caution regarding the security of transmitted data to prevent misuse by the VPN provider